Occupational risk factors associated with respiratory symptoms among tannery workers in Mojo town, Southeast Ethiopia, 2018: a comparative cross-sectional study - Dalju, Innawu; Dessie, Awrajaw; Bogale, Laekemariame; Mekonnen, Tesfaye Hambisa (Multidisciplinary Respiratory Medicine, 2019)
Introduction: Work-related respiratory diseases (WRDs) account for 10–20% of all chronic respiratory illnesses affecting hundreds of millions of people of all ages. Tannery industries are often associated with hazardous working conditions favourable for respiratory conditions. However, information about the prevalence and occupational factors that predispose to respiratory symptoms is meagre in Ethiopia. This study aimed to investigate the magnitude and risk factors associated with work-related respiratory symptoms among tannery industry workers in Mojo town, Ethiopia. Methods: A comparative cross-sectional study was conducted from March to May 2018. A total of 602 (299 exposed to tannery factories) and 303 unexposed (civil servants) were included using the stratified sampling method. The British Medical Research Council (BMRC) questionnaire was pretested and interviewer-administered for data collection. A binary logistic regression analysis was performed to identify the factors associated with respiratory symptoms. The significance of associations was ascertained at a < 0.05 p and adjusted odds ratio with a 95% CI was computed to evaluate the strength of associations. Results: The prevalence of respiratory symptoms among exposed workers was 27.1% [95% CI (21.7, 32.1)] and 8.3% [95% CI (5.3, 11.6)] among unexposed workers in the previous 12 months and the prevalence was significantly different (X2 = 36.82; p < 0. 00001). The odds of developing respiratory symptoms was 3.37 times higher among tannery workers than unexposed workers [AOR: 3.37; 95% CI (1.71, 6.46)]. Female sex [AOR:1.80; 95% CI (1.24, 3.34)], temporarily workers [AOR = 3.43; 95% CI (2.63, 7.95)], working in a poorly ventilated working unit [AOR = 1.88; 95% CI (1.22, 3.98)], absence of occupational health and safety training [AOR = 2.37; 95% CI (1.14, 4.92)], and not using personal protective equipment [AOR = 2.30; 95% CI (1.25, 3.46)] were significant factors. Conclusion: The prevalence of respiratory symptoms was higher among exposed workers compared to unexposed ones. Sex, employment status, ventilation of working units, absence of occupational health and safety training, and not using personal protective equipment were the factors associated with occupational-related respiratory symptoms. Strategies targeting health and safety training, creating awareness on the use of personal protective equipment, and improving workplace conditions, like the provision of adequate ventilation are useful means for assuaging the condition.